2017
DOI: 10.1111/jace.15378
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on nano‐particles reinforced oxide glass

Abstract: Energy release rate and fracture toughness of amorphous aluminum nanoparticles reinforced soda‐lime silica glass (SLSG) were measured by performing fracture simulations of a single‐notched specimen via molecular dynamics simulations. The simulation procedure was first applied to conventional oxide glasses and the accuracy was verified with comparing to experimental data. According to the fracture simulations on three models of SLSG/‐Al2O3 composite, it was found that the crack propagation in the composites is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 53 publications
(94 reference statements)
0
29
1
Order By: Relevance
“…The boundary atoms were fixed in the other two directions. The fracture simulation is described in further detail in Ref …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary atoms were fixed in the other two directions. The fracture simulation is described in further detail in Ref …”
Section: Methodsmentioning
confidence: 99%
“…The fracture simulation is described in further detail in Ref. 35 Figure 5 shows examples of the SEM images obtained by FIB-SEM. In these figures, the dark areas correspond to the hexagonal CaAl 2 Si 2 O 8 crystals, whereas the bright spots observed in the center of the crystals are metallic molybdenum particles.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…E y is 80.7 GPa estimated from the slope of the S‐S curve of the larger composite model (see Figure ), and Poisson's ratio is assumed to be 0.23. Detail of the estimation procedure can be found in our previous work . The S‐S curve of Type‐C apparently demonstrates brittle fracture because the stress sharply drops beyond the stress peak as the strain increases.…”
Section: Resultsmentioning
confidence: 99%
“…To initiate an initial crack propagation by uniaxial loading, a constant velocity of 0.1 m/s was imparted to the atoms located within 5 Å from the both sides of the simulation cell. The velocity is vary fast in comparison with experimentally available deformation speed; however, our previous study, which has examined fracture of soda‐lime silica glass, revealed that the simulation procedure with the same velocity can reproduce experimental fracture toughness within reasonable accuracy . The MD unit cell has sufficient spaces in X and Z directions for avoiding interaction among atoms in the both edges, and periodic boundary condition was considered in all directions to calculate electrostatic interaction by the Ewald method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation